Amberlite IR-120H: An improved reusable solid phase catalyst for the synthesis of nitriles under solvent free microwave irradiation - Varghese, Anitha; Nizam, Aatika; Kulkarni, Rajani; George, Louis (European Journal of Chemistry, 2012)
An efficient green protocol has been developed for the conversion of a range of aldehydes to the corresponding nitriles using a solid-phase reusable catalyst combined with microwave irradiation. The highlighting features of this method are short reaction time, environmentally compatible, reusability of the catalyst and good product yield.